Analysis of the Halalance Aspects of the Product in Pak Gendut Meatball Noodles in Banyuajuh Village, Kamal Kec in the Perspective of Sharia Business Feasibility Study - Sholahuddin (Penerbit Hellow Pustaka, 2024)
This research aims to gain an in-depth understanding of various aspects relevant to the halalness of MSME food products. This research method uses qualitative research. The results of the research show that the business feasibility study analysis in developing MSME food products must ensure halal products, MSMEs in the food sector must implement various production practices that meet applicable halal standards. That the results of this research explain the halal aspect of Pak Fat's meatball chicken noodles can be seen from the perspective of compliance with Islamic law which includes halal substances, halal how to obtain them, halal how to process them, halal in storing them and halal in serving. In order to produce halal products as stated in the JPH Law Article 1 paragraph 3, it must go through a halal product process which includes providing materials, management, storage, packaging, distribution, sales and presentation of the product so as to guarantee the halalness of the product. The results of this research conclude that the halal aspect of the Pak Gendut meatball chicken noodle product in Banyuajuh village, Kamal district, Bangkalan has fulfilled the halal aspect of Islamic law.